The Implementation of School Based Inclusive Curriculum in Teaching Learning English for Slow Learners - Erwina Tri Astuti (Presscience, 2022)
This research was conducted in an attempt to analyze the teacher’s understanding of School Based Inclusive Curriculum, describe the implementation of School Based Inclusive Curriculum, also to describe the problems encountered by the English teachers in implementing School Based Inclusive Curriculum at SMP Muhammadiyah I Sleman in the academic year 2017/2018.The setting of the research was in seventh and eight grade, and there were two teachers as the subjects. The research used descriptive qualitative method with in three ways collected data by doing the observation, in-depth interview and documentation.This study revealed that the teachers under study needs to improve their understanding of School Based Inclusive Curriculum, their ability in designing English syllabus and lesson plan as well as their ability in implementing School Based Inclusive Curriculum in more contextualized learning activities.The implementation of School Based Inclusive Curriculum at SMP Muhammadiyah I Sleman was succeefully but there were still some weakness and some problems to be solved. And the problems encountered the teachers can be categorized into three types; those are 1) problem in planning, 2) problem in implementing Inclusive Curriculum, 3) problem in evaluation.